Capillary electrophoresis and nanomaterials - Part I: Capillary electrophoresis of nanomaterials - Adam, Vojtech; Vaculovicova, Marketa (Electrophoresis, 2017)
Nanomaterials are in analytical science used for a broad range of purposes, covering the area of sample pretreatment as well as separation, detection, and identification of target molecules. This part of the review covers capillary electrophoresis (CE) of nanomaterials and focuses on the application of CE as a method for characterization used during nanomaterial synthesis and modification as well as the monitoring of their properties and interactions with other molecules. The heterogeneity of the nanomaterial family is extremely large. Depending on different definitions of the term Nanomaterial/Nanoparticle, the group may cover metal and polymeric nanoparticles, carbon nanomaterials, liposomes and even dendrimers. Moreover, these nanomaterials are usually subjected to some kind of surface modification or functionalization, which broadens the diversity even more. Not only for purposes of verification of nanomaterial synthesis and batch-to-batch quality check, but also for determination the polydispersity and for functionality characterization on the nanoparticle surface, has CE offered very beneficial capabilities. Finally, the monitoring of interactions between nanomaterials and other (bio)molecules is easily performed by some kind of capillary electromigration technique.
Keywords: Surface Properties; elektroforéza kapilární; dendrimery; Liposomes; kovové nanočástice; nanostruktury; Metal Nanoparticles; Dendrimers; povrchové vlastnosti; liposomy; polymery; Porosity; poréznost; Polymers; uhlík; Nanostructures; Electrophoresis, Capillary; Carbon